Experimental Investigations of the Removal of Methylene Blue from Waste Water using Agricultural Adsorbant - Mandake, Manoj B.; Walke, Santosh; Naniwadikar, Makarand; Patil, Ganesh; Jadhav, Sandhya D. (International Journal of Membrane Science and Technology, 2023)
Abstract: The colored organic or inorganic chemical compounds which can impart colour to other substance are the Dyes which did significant applications in the most industrial sectors like the textile industry, leather industry, paper industry, plastic, foodstuff industry etc, to impart color to their products. Due to the large volume of dye use in these businesses, a significant quantity of wastewater containing colored organics is generated. Because of insufficient dye-fiber fixation, during the dyeing process, half of the dye is lost in the wastewater. Peanut and rice husk are used to absorb MB from water. Initial Methylene Blue concentration, Peanut and Rice Husk dose, and pH were monitored and compared to current adsorbents to identify the optimal removal conditions. The equilibrium amount of MB adsorbed at time t (min) for rice husk and peanut hull are obtained as 5.1 and 5.19 mg/g respectively. As part of the research, an intra-particle diffusion model was implemented to regulate the mass transfer model's rate-controlling step mechanism. Keywords: Waste Water, Methylene Blue, Peanut Hull, Rice Husk, Adsorption.